Effect of laser welding speed on pore formation in AA 6061 T6 alloy - Is, Emine Gundogdu; Topuz, Polat; Akman, Erhan; Yilmaz, Muharrem (CARL HANSER VERLAG, 2020)
In this study, 6 mm thick plates of Al 6061 T6 alloy are joined by laser welding at four welding speeds (40 mm x s(-1), 35 mm x s(-1), 25 mm x s(-1), and 20 mm x s(-1)). The welded joints are made using a 4000 W fiber laser welding machine. The effect of laser welding speed on the pores formed in the weld seam was investigated. In this manner, it was found that with a change in laser welding speed the amount of pores formed in the structure also changed. In addition, after the welding process, macroscopic examinations, tensile tests and the hardness tests were made. As a result of the experiments performed, it was determined that, the laser welding speed was highly effective for pore formation.
Keywords: Al 6001 T6 alloy; laser welding; pores; welding speed; MECHANICAL-PROPERTIES; ALUMINUM-ALLOY; HEAT-TREATMENT; MICROSTRUCTURE; GAS; STRENGTH; QUALITY; Materials Science